Digital Watermarking in Medical Images - Jasni, Mohamad Zain (2005)
This thesis addresses authenticity and integrity of medical images using watermarking. Hospital Information Systems (HIS), Radiology Information Systems (RIS) and Picture Archiving and Communication Systems (PACS) now form the information infrastructure for today’s healthcare as these provide new ways to store, access and distribute medical data that also involve some security risk. Watermarking can be seen as an additional tool for security measures.